PENGARUH LIKUIDITAS, SOLVABILITAS, NET PROFIT MARGIN DAN TOTAL ASSET TURNOVER TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSAK EFEK INDONESIA PERIODE 2016-2019 - Buulolo, Mesra Hati; Naibaho, Febyola Dewanty; Simorangkir, Enda Noviyanti (2021)
The economic condition in Indonesia is currently in a period of development which is quite good, this can be seen from the number of companies that are growing and continues to grow, one of which is in manufacturing companies. This research using a sample of 300 manufacturing companies by analyzing performance financial statements that have been audited by public accountants for the period 2016 - 2019. This study uses secondary data with purposive sampling method. The method of analysis using multiple linear regression method. Result of This study shows that simultaneously liquidity, solvency, net profit margin, and total asset turnover have a significant effect on the value of the company. Partially, the liquidity variable affects the value of company. While the solvency turnover variable has a negative effect jdan significant to profitability. Net profit margin and total asset turn over are not influential and significant to the value of the company. Coefficient test results determination obtained an adjusted R Square value of 0.175 or 17.5%, which means the dependent variable, namely the value of the company can be explained by variations The three independent variables are 17.5%, while the remaining 82.5% is explained by other factors not examined in this study.